Aplikasi GMP dalam Produksi Garam Konsumsi Beryodium - Nami Lestari (Balai Riset dan Standardisasi Industri Samarinda, 2016)
The main objective of Good Manufacturing Practise (GMP) implementation is products with quality, nutrition and for all consumers. GMP implementation is guided by the regulation of health minister (SK. Menteri Kesehatan No. 23/MEN-KES/SK/I/1978). This regulationexplains specifically about a better control process for good industry.The important aspects for GMP implementation are location. building.equipment sanitation, material/ingredients, end products, material packaging, labeling, storage and maintenance. The aspects can be applied on consumption salt industries. By implementation GMP, production process have been done to consumption salt products that is in accordance with SNI 01 -3556 - 2000 requirements.